TeO2-BaO-Bi2O3 tellurite optical glasses I.- Glass formation, structural, thermal and optical properties - Hrabovský, Jan; Svoboda, Roman; Frumarová, Božena; Beneš, Ludvík; Šlang, Stanislav; Dedic, V (Elsevier Science BV, 2024)
The present study investigates the glass-forming ability (GFA), structural, thermal, and optical properties of the TeO2-BaO-Bi2O3 (TeBaBi) glass system, focusing on the mutual substitution trends of its constituent compounds. Prepared glasses were synthesized by the melt-quenching method at 900 degrees C and the GFA was extended by chemical compositions with lower TeO2 (55-85 mol.%) and higher Bi2O3 (5-15 mol.%) content via optimization of the synthesis process. The introduction of BaO and/or Bi2O3 results in the increase of the glass transition temperature (T-g approximate to 327-384 degrees C), molar volume (V-g approximate to 28.9-33.1 cm(3)mol(-1)) and optical basicity (OB approximate to 0.97-1.03). Prepared TeBaBi glasses exhibit satisfactory thermal stability and wide spectral region of optical transparency from 0.4-6.5 mu m with observed narrowing of optical window with higher TeO2 content. Compositional evolution of T-g maybe described for the TeBaBi glasses using multilinear regression analysis with high correlation (r >= 0.995) across the whole GFA region. The structure of studied TeBaBi glasses was investigated by Raman scattering and directly compared to the TeO2-ZnO-BaO (TZB) glass system prepared and characterized under identical conditions. Structural analysis revealed a similar degree of internal glass structure transformation regardless of whether a divalent zinc cation or trivalent bismuth cation is present.
TeO2-BaO-Bi2O3 tellurátová optická skla I.- Tvorba skla, strukturní, tepelné a optické vlastnosti
Keywords: TeO2-BaO-Bi2O3; Glass-forming ability; Optical properties; Thermal properties; Tellurite glasses; Glass structure; TeO2-BaO-Bi2O3; optické vlastnosti; skla; struktura; tepelné vlastnosti